2020
DOI: 10.31557/apjcp.2020.21.10.2941
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 G870A Polymorphism: Relation to the Risk of ALL Development, Prognosis Impact, and Methotrexate Cytotoxicity

Abstract: Nowadays, Pharmacogenomics tests, including Genome-wide association studies (GWAS), have a direct identification role in genetic alterations, treatment efficacy, cytotoxicity, prognosis, etc. However, the current knowledge gives little data about how genomic determinants can affect ALL susceptibility, chemotherapy, and chance of relapse (Wu and Li, 2018). Methotrexate (MTX) forms the backbone of maintenance cycles in childhood acute lymphoblastic leukemia (ALL) chemotherapy, including interim maintenance (Mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In 2020, El Menshawy et al collected 100 individuals from Egypt (50 ALL cases and 50 controls) and investigated the contribution of CCND1 rs9344 genotype to methotrexate cytotoxicity, and survival rates. They found that the AA genotype was associated with a higher risk of developing ALL compared to the control group; no notable association was found between CCND1 genotypes, methotrexate hepatotoxicity and ALL survival rates (41). The metaanalysis of the publications of Howe, Hou, and Bedewy, found a significant association between the CCND1 rs9344 genotype and leukemia (42).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, El Menshawy et al collected 100 individuals from Egypt (50 ALL cases and 50 controls) and investigated the contribution of CCND1 rs9344 genotype to methotrexate cytotoxicity, and survival rates. They found that the AA genotype was associated with a higher risk of developing ALL compared to the control group; no notable association was found between CCND1 genotypes, methotrexate hepatotoxicity and ALL survival rates (41). The metaanalysis of the publications of Howe, Hou, and Bedewy, found a significant association between the CCND1 rs9344 genotype and leukemia (42).…”
Section: Discussionmentioning
confidence: 99%
“…According to The cBioPortal for Cancer Genomics database analysis of samples with mutation data in pan-cancer (TCGA PanCancer Atlas Studies), the mutation frequency of CCND1 in patient is 6% [81,82]. Plenty of studies have shown that the G870A mutation is the most common splice mutation in CCND1, and is associated with the risk, prognosis, and treatment of multiple cancers [20,22,23]. The G870A mutation has been determined to be related to the risk of a variety of cancers such as breast cancer [83], liver cancer [84], colorectal cancer [85], bladder cancer [86], endometrial cancer [87], esophageal and gastric cardiac cancer [88].…”
Section: Mutation Of Ccnd1 Genementioning
confidence: 99%
“…The amplification and/or overexpression of CCND1 have frequently been found in a variety of cancers [3][4][5][6][7][8][9][10][11][12][13][14]. There are a large number of mutations in CCND1, which are closely related to the occurrence, development, prognosis, and treatment of cancers [15][16][17][18][19][20][21]. There are four major mutation types of CCND1, including missense mutation, truncating mutation, inframe mutation, and splice mutation [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that alterations in CCND1 gene expression, including overexpression, underexpression, and variants, are associated with the development and poor prognosis of CRC ( 58 60 ), particularly the G870A mutation ( 60 ). This mutation is the most common splice mutation in CCND1 ( 61 , 62 ) and results in the generation of two CCND1 isoforms through alternative splicing: full-length CCND1a and divergent C-terminal CCND1b ( 63 , 64 ). It is widely accepted that an imbalanced CCND1a/b ratio or high expression of CCND1b is closely linked to the development of cancer.…”
Section: Tumor-associated Splicing Variants In Crc: From Roles To Pot...mentioning
confidence: 99%